CORPUS-BASED ANALYSIS OF MORPHOLOGICAL CHANGES IN THE ENGLISH LANGUAGE (International journal of artificial intelligence, 2026)
This article presents a comprehensive corpus-based analysis of morphological changes in contemporary English. Drawing on data from multiple large-scale corpora spanning the period 2000-2024, the study identifies systematic patterns of morphological innovation, simplification, and analogical extension. The analysis reveals significant transformations in derivational morphology, inflectional regularization, and compounding processes. Particular attention is devoted to changes accelerated by digital communication, globalization, and language contact. The findings demonstrate that English morphology is undergoing measurable transformation, with implications for linguistic theory, language teaching, and natural language processing applications.